Implementasi Model Pembelajaran Kontekstual Menggunakan Media Klinometer untuk Meningkatkan Hasil Belajar Matematika Siswa - Muhammad Azkal Azkiya; Maya Rayungsari; Dewi Nurmalitasari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to enhance students' mathematics learning outcomes by implementing a contextual learning model utilizing clinometer paraji as a teaching aid. This study employs Classroom Action Research (CAR), which consists of two cycles, each involving the stages of planning, implementation, observation, and reflection. The participants in this study were grade X students from SMK Yadika Pasuruan. Data collection was carried out through observations of teacher and student activities, tests to measure learning outcomes, and student response questionnaires regarding the applied learning model. The findings reveal that the contextual learning model using clinometer paraji media effectively improves students' mathematics learning outcomes. Furthermore, students showed enthusiasm and increased interest in mathematics when learning through this approach. Therefore, the clinometer-based contextual learning model is a practical and effective method for teaching mathematics.